2023
DOI: 10.1186/s12913-023-09363-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the stringency of COVID-19 containment policies and health service disruptions in 10 countries

Abstract: Background Disruptions in essential health services during the COVID-19 pandemic have been reported in several countries. Yet, patterns in health service disruption according to country responses remain unclear. In this paper, we investigate associations between the stringency of COVID-19 containment policies and disruptions in 31 health services in 10 low- middle- and high-income countries in 2020. Methods Using routine health information systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic has caused unprecedented disruptions in various aspects of gastroenterology healthcare services worldwide [ 66 ], emphasizing the need to modify the delivery methods of healthcare services [ 67 ] to implement a proactive approach to care. The health services most affected were those dealing with the management of chronic diseases [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has caused unprecedented disruptions in various aspects of gastroenterology healthcare services worldwide [ 66 ], emphasizing the need to modify the delivery methods of healthcare services [ 67 ] to implement a proactive approach to care. The health services most affected were those dealing with the management of chronic diseases [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pitayarangsarit et al conducted a web-based survey on 169 health facilities’ directors in Bangkok. They found that Bangkok’s healthcare services for non-communicable diseases were critically disrupted during the pandemic [ 7 ]. A multi-country study by Reddy pointed to a slight increase (2.73%) in the monthly volume of newborn and maternity care in Thailand during 2020 compared to the average monthly volume a year before [ 8 ].…”
Section: Introductionmentioning
confidence: 99%